(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This study investigated the role of professional codes of ethics in guiding librarians in discharging their statutory duties in academic libraries in Port Harcourt, Rivers State, Nigeria. Using a descriptive survey design, the study involved 62 academic librarians from the University of Port Harcourt, Rivers State University, and Ignatius Ajuru University of Education. A structured questionnaire was used for data collection, with a high return rate of 87.1%. The reliability of the questionnaire was confirmed with a Cronbach alpha coefficient of 0.84. Descriptive statistics, including mean and standard deviation, were employed for data analysis. The findings revealed that while the professional code of ethics significantly guides librarians in promoting fairness, confidentiality, and accountability, gaps remain in awareness and enforcement. The study recommends regular ethics training, better supervision, and a system of rewards and penalties to enhance the adherence to ethical standards in academic libraries.